GENETIC DIVERSITY STUDIES FOR YIELD, ITS COMPONENTS AND QUALITY TRAITS IN BLACKGRAM (Vigna mungo (L). Hepper) - D. BHARATHI*, K. HARIPRASAD REDDY, D. MOHAN REDDY, P. LATA; B. RAVINDRA REDDY (The Journal of Research ANGRAU, 2019)
A total of 89 blackgram accessions were subjected to D2 analysis to assess the diversity for 18 quantitative traits. The genotypes were grouped into 14 clusters. Cluster IV consisted of maximum number of accessions (26) followed by cluster I (23), III (16) ,II (10) and cluster X (5).The clusters viz., V, VI, VII, VIII, IX, XI, XII, XIII and XIV consisted only one accession each. The inter-cluster distances were greater than intracluster distances, revealing that considerable amount of genetic diversity existed among the accessions. Maximum inter cluster distance was observed between cluster IX and X (815.75) followed by clusters III and X (752.52), cluster II and X (746.95) and cluster X and XII (654.83). Genotypes belonging to these diversified clusters could be utilized in the hybridization programme to get desirable recombinants segregating generations. Among all the characters, methionine content contributed maximum (32.33%) towards the in divergence followed by lysine content (27.20%) and tryptophan content (16.32%